2005
DOI: 10.1007/s11307-005-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of [14C]FMAU, [3H]FEAU, [14C]FIAU, and [3H]PCV for Monitoring Reporter Gene Expression of Wild Type and Mutant Herpes Simplex Virus Type 1 Thymidine Kinase in Cell Culture

Abstract: This combination of high accumulation and high selectivity for both HSV1-tk and HSV1-sr39tk makes suitably radiolabeled FEAU a promising candidate as a radiotracer for imaging HSV1-tk/HSV1-sr39tk gene expression in living subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Another 5-substituted nucleoside, FEAU, was also developed as an anti-Herpes Simplex agent [33,34] FEAU demonstrated lower cellular toxicity but is still as effective as FIAU to treat cells infected with Herpes Simplex Virus. We [8] and others [35] Mutant HSV1-tk's were initially developed to more effectively utilize acyclovir and ganciclovir (GCV) and to less effectively utilize thymidine to allow for more effective suicide gene therapy [36]. We have attempted to improve the sensitivity of imaging reporter gene expression by using an alternate substrate such as GCV, PCV, and FHBG and the mutant reporter gene HSV1-sr39tk [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 5-substituted nucleoside, FEAU, was also developed as an anti-Herpes Simplex agent [33,34] FEAU demonstrated lower cellular toxicity but is still as effective as FIAU to treat cells infected with Herpes Simplex Virus. We [8] and others [35] Mutant HSV1-tk's were initially developed to more effectively utilize acyclovir and ganciclovir (GCV) and to less effectively utilize thymidine to allow for more effective suicide gene therapy [36]. We have attempted to improve the sensitivity of imaging reporter gene expression by using an alternate substrate such as GCV, PCV, and FHBG and the mutant reporter gene HSV1-sr39tk [14].…”
Section: Discussionmentioning
confidence: 99%
“…We [8] and other groups [9,15] have recently reported that radiolabeled FEAU, a 5-ethyl-substituted derivative of [ 18 F]FMAU, demonstrates high sensitivity and selectivity to both HSV1-tk and HSV1-sr39tk in cell uptake studies. Unlike [ 18 F]FMAU [16] that binds mainly to mammalian tk and is used as a marker for cell proliferation, [ 18 …”
Section: Introductionmentioning
confidence: 98%
“…Recently, others have demonstrated that FEAU has the highest uptake ratio between tk-positive transduced cells and wild-type cells when compared with FHBG, FIAU, FMAU, FHPG and FLT 24 . It has been reported that a combination of high accumulation and high selectivity for both HSV1-tk and HSV1-sr39tk makes FEAU a promising candidate for PET imaging of HSV-tk gene expression 25 . [ 18 F]FEAU has also been used to monitor the response of tumors using PETafter systemic Sindbis/tk (vector) treatment as a basis for determining the levels of tissue distribution of vectors in living animals 26 .…”
Section: Introductionmentioning
confidence: 99%
“…18 F-9-(4-18 F-fluoro-3-hydroxymethyl-butyl) guanine (FHBG) [5,70,71]. One of the advantages of enzymatic reporter gene systems, such as -tk enzyme, is the signal amplification that occurs as a result of imaging probe trapping and accumulation.…”
Section: Radionuclide Imagingmentioning
confidence: 99%